Evaluation of sample preparation procedures and krypton as an interference standard probe for arsenic speciation by HPLC-ICP-QMS - Amaral, Clarice D. B.; Dionísio, Amália G. G.; Santos, Mirian C. [UNESP]; Donati, George L.; Nóbrega, Joaquim A.; Nogueira, Ana R. A. (Royal Society of Chemistry (RSC), 2013)
Different conditions of extraction using water, a methanol-water mixture and nitric acid solutions were evaluated for speciation of As(iii), As(v), DMA and MMA in plant samples that previously received As(v) after being sown and emergence was investigated. Microwave-assisted extraction (MAE) using diluted nitric acid solutions was also performed for arsenic extraction from chicken feed samples. The separation and determination of arsenic species were performed using HPLC-ICP-MS. The interference standard method (IFS) using 83Kr+ as the IFS probe was employed to minimize spectral interferences caused by polyatomic species, such as 40Ar 35Cl+. The extraction procedures tested presented adequate extraction efficiencies (90%), and the four arsenic species evaluated were found in plant samples. Extractions with diluted nitric acid solution at 90 °C were the most efficient strategy, with quantitative recoveries for all four As species in plant tissues. On the other hand, the methanol-water mixture was the solvent with the lowest extraction efficiency (50-60%). For chicken feed samples, MAE at 100 °C for 30 min resulted in an extraction efficiency of 97% and only As(v) was found, without any species interconversion. The IFS method contributed to improving precision and limits of detection and quantification for all tested extraction procedures. Significant improvements on accuracy were obtained by applying the IFS method and recoveries between 77 and 94%, and 82 and 93% were obtained for plant extracts and chicken feed samples, respectively. This journal is © 2013 The Royal Society of Chemistry.